2016
DOI: 10.1002/pts.2216
|View full text |Cite
|
Sign up to set email alerts
|

Modified Method for Dynamic Stress-Strain Curve Determination of Closed-Cell Foams

Abstract: The paper presents a modified method for the non‐linear dynamic stress‐strain curve determination with the use of cushion curves provided by the manufacturers of closed‐cell foams. This method consists of two main stages: stage 1 – the cushion curves transformation to the coordinate system of dynamic stress‐energy density, combined with the cubic b‐spline curve approximation, and stage 2 – development of the dynamic stress‐strain curve considering that the area under the curve is equal to the energy density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…We have shown that the material behaviour can be adjusted to represent the impact response by calibrating the model using a viscous damping coefficient predicted from the shock pulse. This approach works well, since the dynamic stress strain relationship does not significantly deviate from the quasi‐static stress strain relationship in the polystyrene foam …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have shown that the material behaviour can be adjusted to represent the impact response by calibrating the model using a viscous damping coefficient predicted from the shock pulse. This approach works well, since the dynamic stress strain relationship does not significantly deviate from the quasi‐static stress strain relationship in the polystyrene foam …”
Section: Resultsmentioning
confidence: 97%
“…These modelling efforts significantly reduced the necessary time to determine cushion curves from the experimental procedures outlined in ASTM D1596 . Initially, the mathematical predictions were based on an energy balance during impact and evolved to both analytical solutions and numerical simulations of the impact process . However, with the exception of finite element simulations, these efforts were based on a lumped parameter approximation of the cushioning foam and impacting mass.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the limit-state function of the system can be obtained by (21), and the FORM can be used to analyze the acceleration response reliability of the package. e reliability index is obtained by (13), the vector a(t) is obtained by (10), h(t) is obtained by (8), the vector s(t) can be obtained by (26), and the acceleration response rst passage probability of the package is obtained by (4). In this example, the rst passage failure probability of the package is calculated and shown in Figure 5.…”
Section: Examplementioning
confidence: 99%
“…Zhong et al [3] took the friction force into account and proposed a new friction equivalent drop theory; this theory provided a new theoretical basis for experimental analysis of structural cushioning materials. To model the closed-cell foam dynamic properties efficiently in the finite element method, Piatkowski and Osowski [4] presented a modified method for the nonlinear dynamic stress-strain curve determination with the use of cushion curves. In [5,6], new methods for evaluating cushioning properties in drop shock conditions were also presented.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the light weight and good restitution properties, polymeric foam has been extensively applied for energy absorption and packaging design . Polyethylene (PE) foam is the preferred choice in terms of its outstanding recovery characteristics to withstand multi‐impact by comparing with polystyrene (PS) foam .…”
Section: Introductionmentioning
confidence: 99%